Lesbian, Gay, Bisexual, and Trans Aging in a U.K. Context: Critical Observations of Recent Research Literature. (July 2019) - Almack, Kathryn; King, Andrew
In this article, we provide critical observations of empirical research from leading U.K. researchers relating to the lives of lesbian, gay, bisexual, and trans older adults. We suggest learning that may be applied in differing global contexts as well as contributing to the development of an international evidence base. We illustrate the importance of paying attention to distinct health and care systems and legislation, which present global differences as well as similarities in terms of lesbian, gay, bisexual, and trans people's perceptions and access to resources. With this contextual background, we then discuss the cutting-edge U.K. research in this field from 2010 onward. We identify key strengths including the contribution our evidence has made to policy and practice and the development of theoretical insights such as the impact of intersectionality. The article concludes with a discussion of future research in this field which has relevance at national and international levels.